PRAGMATICS AND SPEECH ACT THEORY - Zebokhon Musaeva Muzaffarovna (Galaxy International Interdisciplinary Research Journal, 2022)
The steady development of science and technology in general, and linguistic science in particular, is linked not only to the resolution of current scientific problems, but also to state features such as internal and foreign policy, and the upkeep of state educational standards, all of which are generators of progress in a social and economic society. It creates a civilization that can easily adapt to the modern world.